2011
DOI: 10.1118/1.3618731
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of phase retrieval methods in x‐ray phase contrast imaging: A comparison

Abstract: Purpose: The robustness of the phase retrieval methods is of critical importance for limiting and reducing radiation doses involved in x-ray phase contrast imaging. This work is to compare the robustness of two phase retrieval methods by analyzing the phase maps retrieved from the experimental images of a phantom. Methods: Two phase retrieval methods were compared. One method is based on the transport of intensity equation (TIE) for phase contrast projections, and the TIE-based method is the most commonly used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…(5) and called this as the phase-attenuation duality (PAD). 21 We found that when the phase-attenuation duality holds, the x-ray propagation equation gets simplified and the phase map can be retrieved from just a single phase-sensitive projection I ( r D ) of the imaged object: 21,22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) and called this as the phase-attenuation duality (PAD). 21 We found that when the phase-attenuation duality holds, the x-ray propagation equation gets simplified and the phase map can be retrieved from just a single phase-sensitive projection I ( r D ) of the imaged object: 21,22 …”
Section: Methodsmentioning
confidence: 99%
“…21 Recently, we have theoretically and experimentally demonstrated that the PAD-based phase retrievals are robust against the noise, in a stark contrast to the TIE-based method that is unstable in the presence of noise in images. 22 Of course, in order for breast tissues to fulfill the phase-attenuation duality condition, the tube voltages should be set to as high as 120-150 kVp, grossly different from the tube voltages employed in current mammography, where tube voltages used are lower than 40 kVp. Although the attenuation-based tissue contrast gets much reduced at 120-150 kVp, the phase-contrast extracted from the phase retrieval will compensate for the attenuationcontrast loss associated with the use of high tube voltages.…”
Section: Is a Pseudodifferential Operator The Action On A Function Gmentioning
confidence: 99%
“…This stark comparison shows that the conventional TIE-based phase retrieval method is unstable against the noise in the wrap's projection images, while the AP-based phase retrieval method is shown in the experiment to be superior to the TIE-based method for the robustness in performing the phase retrieval. For details, please refer to [Yan, Wu, Liu 2011].…”
Section: Develop the Phase Retrieval Methodsmentioning
confidence: 99%
“…This result advanced the understanding of the image contrast mechanism of phase contrast tomography. For details, please refer to [Yan and Wu 2011]. …”
Section: Develop the Phase Retrieval Methodsmentioning
confidence: 99%
See 1 more Smart Citation